Structural insights and ADMET analysis of CAFI: hydrogen bonding, molecular docking, and drug-likeness in renal function enhancers - P. Divya; V. S. Jeba Reeda; P. Rajkumar; A. Amala Jeya Ranchani; R. Shahidha; Mudassar Shahid; Nazia Siddiqui; Saleem Javed (BMC Chemistry)
Abstract Using quantum chemical calculations, spectroscopic methods, and molecular docking analysis, this work explores the electronic, structural, vibrational, and biological characteristics of CAFI. Intramolecular hydrogen bonding between the methyl and C = O groups (with bond lengths less than 3 Å) was detected, affirming molecular stability. Corresponded with the theoretical expectations, FT-IR and UV spectra corroborating CAFI’s chemical stability. Frontier molecular orbital study indicated HOMO-LUMO energy gaps between 4.227 eV (gas) and 4.792 eV (ethanol), underscoring charge transfer activity. Molecular docking revealed CAFI as the most potent binder to proteins that stimulate kidney function, with a binding energy of -4.08 kcal/mol and sustained hydrogen bonding connections. ADMET analysis confirmed CAFI’s drug-likeness, indicating advantageous absorption, distribution, metabolism, and toxicity characteristics. These findings indicate CAFI as a potential treatment candidate for the regulation of renal function.